Settlement Prediction Based on the Relationship between the Empirical and Analytical Solutions of a Cylindrical Cavity under Undrained Conditions - Pieride Mabe Fogang; Yang Liu; Pengqiang Yu (Advances in Civil Engineering)
Settlements on the ground surface often relate to excavating an underground cavity in cities. Movement on the ground surface can create a void between the wall of the cylindrical cavity and the lining. Thus, this study proposes an approximate solution under undrained conditions, based on the relationship between the empirical and analytical methods for predicting ground settlement around a cylindrical cavity. Based on mathematical formulas, the results obtained by the geometrical representation are then associated with the experimental data. The study revealed that the settlement prediction is related either to ground surface loads or to the ground failure point. The expansion of the cylindrical cavity is solved as a linear elasticity problem using a system of first-order ordinary differential equations containing two components in the Cartesian coordinates. The stress distribution around the cylindrical cavity is evaluated based on a biaxial force. The proposed approaches show that the results (empirical and analytical) obtained are approximately similar. Hence, the relationship between the two methods can be best suited for predicting the settlement around a cylindrical cavity by evaluating both the maximum settlement and the maximum surface displacement.